Correlation of Human Capital and Employees Satisfaction of Hotel Employees' - Helen Grace Legorio (Program Studi S3 Ilmu Manajemen, 2022)
The purpose of this quantitative research was to determine the correlation of human capital in relation to employees’ satisfaction, a survey questionnaire was administered to different hotels in Davao Region with 400 hotel employees, results show that human capital shows a significant relationship with employees’ satisfaction, variable on human capital have a direct significant effect on employees’ satisfaction.